Effects of intraluminal thrombus and wall thickness on wall stress of hypothetical symmetric and asymmetric abdominal aortic aneurysm - Balbarona, Juvy A.
Abdominal aortic aneurysm (AAA) is an irreversible enlargement of the terminal aortic segment affecting 0.4 percent of people over the age of 50. It occurs gradually over a span of years and is considered a health risk as it may rupture if not treated. From a biochemical point of view, AAA rupture occurs when the induced mechanical wall stress exceeds the local minimum strength of the AAA wall. Knowledge of the biochemical behavior of AAA tissue may therefore prove very indispensable in understanding the underlying mechanism behind the changes involved with AAA formation. The purpose of this work is to obtain qualitative information on how wall thickens, intramural thrombus and asymmetry influence aneurysm wall stress. Four sets of three dimensional hypothetically modeled AAA are the subject of this study. A published hyperelastic strain energy function is used as the material model for the AAA wall. Using finite element method, the stress distribution on the aortic wall under systolic pressure is determined for all 16 AAA models. Results showed the distribution of wall stresses, with peak wall stresses located at the inner wall of the AAA, for both axially symmetric and asymmetric models. The stress gradient through the AAA wall shows that the wall strength distribution within any particular AAA is spatially variable. The effect of the aneurismal wall thickens and the incorporation of intramural thrombus showed profound influence on the magnitude and distribution of stresses on AAA wall.
Keywords: Abdominal aortic aneurysm (AAA).; Intraluminal Thrombus